Some linguistic aspects of stuttering in Kannada - Gheetha YV (Journal of All India Institute of Speech and Hearing, 1970)
Studies on the linguistic variables of stuttering are not available in the Indian languages. The present study is an attempt to find some of these linguistic variables of stuttering in Kannada languages.